The Third Coming of French Critical Geographies: Afterword to a Translation - Hessek, Elizabeth Rose (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Critical translation between languages requires consideration not only of the meanings of words, but also of the translator's embeddedness in worlds which assign those meanings. Especially when working with geographic texts, reflecting on the places and spatial experiences that shape our understanding and use of words can be pertinent to creating authentic translations. In translating Yann Calbérac and Marianne Morange and Cécile Gintrac's texts that present an overview of French critical geographies, the translator reflects on ways her own history in French, American, and Canadian academic spaces effects her ability to transfer the nuances of French critical geographies to an Anglophone audience.